Assessment of the impact of climate change and flooding on bridges and surrounding area - Habeeb, Bassel; Bastidas-Arteaga, Emilio (Frontiers in Built Environment, 2023)
Climate change has the potential to significantly impact transportation infrastructure performance. In the case of bridges crossing rivers, climate change could increase the annual river discharge magnitudes and frequency in some regions. Bridges are designed to withstand a maximum flood level (design flood) considering the expected frequencies and magnitudes of floods in the area. The design flood level ensures the safety of the bridge without being damaged against historical flooding levels being repeated. However, flood magnitudes are expected to increase in some regions due to climate change, and therefore, the bridges may not be able to maintain their serviceability and safety, thus, resulting in significant risk to users and economic losses. This problem is approached in this paper by investigating the effects of flooding and climate change on bridges crossing rivers. The input of the proposed methodology is the river flow for various climate change scenarios as well as the topography and bridge characteristics. Flood frequency analysis is used to provide information about the magnitude and frequency of flood discharges when considering climate change. Afterwards, several risk assessment and probabilistic indicators are computed to assess the bridge performance. The proposed methodology is illustrated with a study case in the United Kingdom. The results indicate that the risk of flooding, and associated consequences, would increase for the more pessimistic climate change scenarios. Findings from this study can be used to inform decision making for improving the case study resilience.